2016
DOI: 10.1007/s11187-016-9776-z
|View full text |Cite
|
Sign up to set email alerts
|

R&D profitability: the role of risk and Knightian uncertainty

Abstract: This paper provides the first empirical attempt of linking firms' profits and investment in R&D revisiting Knight's (Risk, uncertainty and profit, Hart, Schaffner & Marx, Boston, 1921) distinction between uncertainty and risk. Along with the risky profit-maximising scenario, identifying a second, offsetting, unpredictable bias that leads to heterogeneous returns to R&D investments is crucial to fully understand the drivers of corporate profits. Consistently with the Knightian theory that relates risk to profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 53 publications
1
26
0
3
Order By: Relevance
“…Moreover, our results support and complement the findings from Aljinović Barać and Muminović [20], who found, on the case of dairy processing industry in Slovenia, Croatia, and Serbia, a negative effect of capital investments on the short-term profitability, also expressed by return on assets, for which, according to the authors, a possible explanation can be found in the time lag between the moment of investment and the moment in the future when investment will generate the profit. Although other researchers have used different measures of profitability in their studies, we can say that in general, the results of this study also support the findings from, for example, Grazzi et al [3], Aw et al [22], Fama and French [25], Yu et al [26], Lööf and Heshmati [27], Johansson and Lööf [28], Amoroso et al [31], Curtis et al [32], who found a positive relationship between capital investments and profitability.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, our results support and complement the findings from Aljinović Barać and Muminović [20], who found, on the case of dairy processing industry in Slovenia, Croatia, and Serbia, a negative effect of capital investments on the short-term profitability, also expressed by return on assets, for which, according to the authors, a possible explanation can be found in the time lag between the moment of investment and the moment in the future when investment will generate the profit. Although other researchers have used different measures of profitability in their studies, we can say that in general, the results of this study also support the findings from, for example, Grazzi et al [3], Aw et al [22], Fama and French [25], Yu et al [26], Lööf and Heshmati [27], Johansson and Lööf [28], Amoroso et al [31], Curtis et al [32], who found a positive relationship between capital investments and profitability.…”
Section: Resultssupporting
confidence: 88%
“…Kapelko et al [30], also on the case of Spanish manufacturing firms, found that capital investments produce a significant productivity change loss in the first year after investment, but thereafter productivity improves, resulting in the U-shape pattern of relationship. Amoroso et al [31], on the case of EU firms, while making distinction between R&D and physical investments, showed that both R&D and physical investments, have a positive effect on the performance, expressed by the operating profit, and that larger firms also get higher returns in the presence of risk. Curtis et al [32], using financial data on mergers and acquisitions, found that capital expenditures, as well as R&D expenditures, have a positive effect on the net profit and future earnings volatility of analyzed firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Para solucionar este problema, la mayoría de los investigadores han recurrido a la utilización de métodos econométricos que requieren de la existencia de una muestra de control, es decir, una muestra de empresas no subvencionadas pero con características similares a las de las empresas perceptoras de ayudas 2 . En ausencia de una muestra de control adecuada, otra de las metodologías más utilizadas es la realización de encuestas ex profeso, donde se pregunta directamente a la empresa beneficiaria sobre el impacto de la ayuda pública sobre su comportamiento 3 . La desventaja fundamental de este tipo de encuestas es que suelen tener un elevado coste de ejecución.…”
Section: Resultados De Los Proyectos De I+d+i En Empresas Con Apoyo Punclassified
“…Ejemplos de este tipo de métodos son el estimador de selección de Heckman, las regresiones de variables instrumentales, los estimadores matching o los estimadores de diferencias-en-diferencias 3. Véase en HUERGo y RoJAS (2014) un panorama de las distintas metodologías empleadas para el análisis de impacto de las ayudas públicas.…”
unclassified
“…Companies compete to have a bigger share of standards in the market (Abernathy and Utterback, 1978). Additionally, there is an enormous amount of uncertainty involved in the product development activities (Amoroso et al, 2015).…”
Section: Technology Life-cyclementioning
confidence: 99%